LABORATORY INVESTIGATION ON GRAVEL AND MIXED BEACHES DURING AN OBLIQUE WAVE ATTACK - Christos Antoniadis (JOURNAL OF COASTAL DEVELOPMENT, 2012)
An experimental investigation into the behavior of gravel and mixed (sand and gravel) beaches was carried out at the 3-D Wave Basin located at Franzius-Institute (Marienwerder) of University of Hannover, at a nominal scale of 1:1. The experiment aimed to provide full scale measurements of cross-shore processes on gravel and mixed beaches, during an oblique wave attack, with uniform slope and a trench. Measurements included sediment transport, cross-shore beach profiles and wave-induced currents, for regular and random wave tests, for both types of beaches. Analysis of both cross-shore and long-shore currents shown interesting behaviour for both gravel and mixed beach, especially at the trench. There were morphological differences between the two types of beach concerning the crest and the step formation, the onshore sediment movement, and the erosion below the SWL, concluding the general difference of their mobility.